Clinical Handbook of Neuromuscular Medicine (Springer International Publishing, 2018)
This concise and practical book provides an overview of neuromuscular disorders in clinical practice. Diagnostic approaches are covered along with patient management strategies in an easy-to-understand and introductory framework. Filling a significant gap in the literature, this resource delivers essential information for neurology trainees and practitioners, as well as anyone interested in learning the fundamentals of this important medical subspecialty.